Management of major viral and fungal diseases affecting temperate food legume crops in the Arab and Mediterranean countries - Kumari, Safaa; Kemal, Seid Ahmed (the Mediterranean Phytopathological Union, 2025)
The production, productivity and quality of temperate food legumes (faba bean, Kabuli chickpea, lentil, and field pea) are affected by several viral and fungal diseases in the Arab and Mediterranean countries. Surveys conducted over the past three decades have shown that the most important diseases affecting food legumes are wilt/root rot disease complex caused by Fusarium spp., Rhizoctonia and Pythium spp., and foliar diseases. In a few countries, parasitic nematodes (Heterodera and Pratylenchus spp.), and Ascochyta blights (Didymella spp.) are the major diseases of chickpea, faba bean and lentil, whereas faba bean suffers from chocolate spot (Botrytis fabae) and rust (Uromyces viciae-fabae). Viruses are emerging production constraints of food legumes where Faba bean necrotic yellows virus (FBNYV), Chickpea chlorotic stunt virus (CpCSV), Beet western yellows virus (BWYV), Bean yellow mosaic virus (BYMV), and Pea seed-borne mosaic virus (PSbMV) are the major ones. These viruses are affecting food legumes individually or as mixed infections. The importance of food legume viruses is mainly associated with increased in aphid activities due to changes in climate and cropping system in the regions. A positive linear correlation has been observed between virus prevalence and aphids that can transmit these viruses. The main aphid species in legume fields were Acyrthosiphon pisum (Harris), Aphis craccivora Koch. and Aphis fabae Scopoli. In addition, several wild species (annual or perennial) were found infected with these viruses and may play an important role in the spread of these viruses. In recent years, virus epidemics have been reported in some Arab countries (such as Egypt, Tunisia, Syria, and Jordan), sometimes causing considerable yield reduction. Significant progress has been made in managing fungal diseases by integrating two or more management options, such as development resistant varieties, production of healthy seeds, adjusting planting dates, seed treatments, selective use of fungicide sprays, and cultural practices that reduce the impact on food legume productivity and quality. Over the past two decades, faba bean genotypes resistant to FBNYV and BLRV, chickpea genotypes resistant to CpCSV and BWYV, and lentil genotypes resistant to FBNYV, BLRV and PSbMV have been successful identified. In addition, a relatively quick and simple plastic house technique was developed to identify resistant genotypes on the basis of relative virus movement and multiplication using Tissue blot immunoassay (TBIA). However, management options remain limited for emerging viruses, the emergence of virulent pathogens mainly for Ascochyta blight on chickpea, and complex soil-borne diseases caused by several parasitic pathogens and nematodes. Further efforts are still needed to develop varieties with multiple disease resistance, integrate new management options supported by digital innovations, establishing regional networks for food legume disease research for development, capacity development, and utilize modern tools, such as diagnostic tools, AI-based early warning and detection systems. Furthermore, more farmer-led participatory research for development is needed to effectively address the key plant health challenges arising from climate and farming systems changes facing food legume production systems in the Arab and Mediterranean countries which is leading to cereal monocropping.